SISTEM PAKAR DIAGNOSA KERUSAKAN PADA MESIN PENDINGIN RUANGAN DENGAN METODE FORWARD CHAINING - Guntur, Guntur; Merlina, Nita (Jurnal Pilar Nusa Mandiri, 2016)
At this time. Air conditioner have been obviously a very basic need to many people. Hence the use of air conditioner likely require regular maintenance, this is what drives development of an expert system to identify air conditioner damage. Expert system is a branch of artificial intelligence that makes extension use of specialized knowledge to solve problems at the level of a human expert. An expert is a person who has expertise in a certain area. This expert system can help find solutions quickly and can save time. Inference method used is a forward chaining , the inference process that initiate search of the premises or in the form of input data lead to the conclusion that symptoms of the damage conclusions and provide solutions on air conditioner damage. The test results are made based on the questionnaire showed that, the program quite useful in providing information about damage to the air conditioner, made consultation more efficient with result that equally same with air conditioner technician.